Issues of personal data management in organizations – GDPR compliance level analysis - Kucęba, Robert; Chmielarz, Grzegorz (Problematyka zarządzania bezpieczeństwem danych osobowych w organizacjach – analiza stopnia zgodności z RODO, 2018)
The paper presents the issues of information and personal data security management in organizations. The authors include in it an analysis of breaches to personal data security in organizations as a vital factor that conditions the necessity to improve the previously applied solutions in this area. Additionally, the paper contains analyses concerning the preparation level of organizations to ensure compliance with the General Data Protection Regulation (GDPR) which is coming into force. The paper constitutes a cognitive query in the scope of the subject matter defined in its title
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 1 (47), s. 58-71
Keywords: personal data; personal data protection; personal data security breaches; GDPR; dane osobowe; ochrona danych osobowych; naruszenie bezpieczeństwa danych osobowych; RODO